Role of disinfection and hand hygiene: a COVID-19 perspective - Roy, Adrija; Parida, Swayam Pragyan; Bhatia, Vikas (International Journal Of Community Medicine And Public Health, 2020)
Coronavirus disease 2019 (COVID-19) being an acute respiratory disease caused by a novel coronavirus (SARS-CoV-2) is transmitted in most instances through respiratory droplets, direct contact with cases, and also through contaminated surfaces/objects. Though the virus survives on environmental surfaces for varied periods, it gets easily inactivated by disinfectants. Therefore, this article aims to highlight the role of surface disinfection and hand disinfection during the COVID-19 pandemic. Disinfection with appropriate and recommended physical or chemical disinfectants will not only reduce the spread of the disease but also play a significant part in flattening the curve. Alcohol-based disinfectants and other chemical disinfectants play major roles. Ether, ethanol, hydrogen peroxide, sodium hypochlorite, other chlorine-containing disinfectants, peracetic acid, chloroform used under appropriate concentrations and techniques are necessary to stop the chain of transmission. Hand disinfection using soap and water or alcohol-based hand rubs are also of equal importance. Irrespective of the importance, the judicious use of disinfectants is also necessary. Therefore, the fastest, easiest, and most effective way to halt or reduce the spread of SARS-CoV-2 the virus resulting in the coronavirus disease (COVID-19) is through surface disinfection and handwashing with soap and water and its role in the COVID-19 pandemic is highly important.